Natural Enemies of Rugose Spiraling Whitefly, Aleurodicus rugioperculatus Martin (Insecta: Hemiptera: Aleyrodidae) in the South Florida Landscape - Siavash Taravati; Catharine Mannion; Holly Glenn; Lance Osborne (EDIS)
Rugose spiraling whitefly was first observed in south Florida in 2009. It has been found in 17 counties in south and central Florida. This whitefly has been reported on more than 60 plant species, which include gumbo limbo, coconut, black olive, avocado, Calophyllum spp., and giant white bird of paradise. This 6-page fact sheet describes the predators and parasitoids found feeding on this whitefly in the south Florida landscape. Written by Siavash Taravati, Catharine Mannion and Holly Glenn, and published by the UF Department of Entomology and Nematology, August 2013.